The Intellectual Authority of Yasin Al-Fadani In The Global Transmission of Hadith - Nur Hamidah Pulungan; Ilham Ramadan Siregar; Yasser Muda Lubis; Mowafg Abrahem Masuwd (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study investigates the intellectual authority and contributions of Shaykh Muhammad Yasin al-Fadani to global hadith scholarship, widely known as Musnid al-Dunyā for his extensive sanad networks in the modern period. It addresses the marginalization of Southeast Asian ulama in dominant narratives of Islamic intellectual history, which emphasize Middle Eastern centers while underrepresenting Nusantara contributions. Using a historical-qualitative approach, this research analyzes primary sources, including al-Fadani’s sanad compilations, ijāzah documents, and scholarly writings, supported by literature on Islamic intellectual networks and hadith transmission. The analysis is framed within transregional epistemic networks and sanad-based authority as a living tradition of knowledge production. The findings show that al-Fadani played a pivotal role in connecting Southeast Asian and Middle Eastern scholarly worlds through teaching, documentation, and systematic transmission of hadith knowledge. His authority was grounded not only in the accumulation of sanad chains but also in his ability to institutionalize transmission practices within modern scholarly contexts. This reflects epistemic agency in which Southeast Asian scholarship actively shapes global Islamic intellectual traditions rather than merely receiving them. Furthermore, al-Fadani transformed classical sanad traditions into a structured epistemological framework compatible with modern Islamic educational systems without severing their traditional foundations. His legacy reconfigures understandings of authority, transmission, and scholarly legitimacy in contemporary hadith studies. Overall, this study re-evaluates Southeast Asian intellectual presence in global Islamic scholarship by positioning al-Fadani as a key figure in preserving, systematizing, and expanding sanad-based knowledge networks.